Analyzing Challenges in Enterprise Resource Planning (ERP) Implementation in a Safety Inspection Company: an IVT2IF DEMATEL Approach - Siraj, Tanvir; Haque, Rashedul; Chowdhury, Saimon; Islam, Nazrul; Biswas, Basudeb; Chowdhury, Kamrul Hasan (Optimality, 2024)
Implementing Enterprise Resource Planning (ERP) systems is crucial for modern businesses, offering integrated solutions that streamline operations and enhance decision-making. However, in specialized sectors such as safety inspection within the Readymade Garment (RMG) industry, ERP implementation presents unique challenges due to the complexity and scope of operations. This research addresses the critical need to understand and systematically address these challenges, particularly in a safety inspection company focused on fire, electrical, structural, and boiler safety. Despite extensive research on ERP implementation in various industries, there is a significant gap in understanding the specific challenges faced by safety inspection companies in the RMG sector. To fill this gap, this study employs the Interval-Valued Type-2 Intuitionistic Fuzzy (IVT2IF) Decision-Making Trial And Evaluation Laboratory (DEMATEL) method to identify, rank, and analyze the interrelationships between ERP implementation challenges. The research identifies fifteen major obstacles, including "Vendor Selection and Management" (D+R = 11.347, D-R = -1.223), "Data Migration" (D+R = 10.194, D-R = -1.891), and "Customization Requirements" (D+R = 11.137, D-R = -0.458). The results highlight "Change Management" (D+R = 8.866, D-R = 1.772) and "Scalability and Future-Proofing" (D+R = 7.370, D-R = 1.753) as the primary causal factors influencing the implementation process. In contrast, "Data Migration" and "Compliance and Security" are significant effect challenges, dependent on successfully managing other factors. By understanding the causal relationships between challenges, companies can prioritize their efforts in key areas to mitigate the most impactful risks during ERP implementation. This approach not only enhances the efficiency and effectiveness of ERP systems but also ensures regulatory compliance and improved decision-making, ultimately contributing to safer working environments in the garment industry.